Guiding and amplification of microwave radiation in a plasma channel created in gas by intense ultraviolet laser pulse. (24th November 2014) - Bogatskaya, A. V.; Smetanin, I. V.; Volkova, E. A.; Popov, A. M.
Abstract: The evolution of non-equilibrium plasma channel created in xenon by powerful KrF-femtosecond laser pulse is studied. It is demonstrated that such a plasma channel can be used as a waveguide for both transportation and amplification of the microwave radiation. The specific features of such a plasma waveguide are studied on the basis of the self-consistent solution of the kinetic Boltzmann equation for the electron energy distribution function in different spatial points of the gas media and the wave equation in slow-varying amplitude approximation for the microwave radiation guided and amplified in the channel.